The Disparity of Criminal Implementation in Case of Child Intercourse and Molestation As Seen From The Perspective of Decidendic Ratio Theory - Fahmy Asyhari (Publikasi Indonesia, 2022)
This study aimed at examining the factors that cause the disparity of punishment in cases of sexual intercourse and molestation of minors, especially in Salatiga City, the impact of the occurrence of criminal disparities, and how the policy model for criminal acts of sexual intercourse and obscenity should be seen from the decidendi theory. The results of the study showed that the disparity in criminal penalties in criminal cases with children as victims is the existence of internal and external factors. Internal factors is in the form of a judge's own personality. While external factor is the legal factor or the legislation itself and the situation factor in the person who is in the perpetrator or defendant. The judge must be careful in seeing, digging, and observing the facts in the trial. Judges must pay attention to the attitude of prudence, avoiding carelessness, both formal and material to technical skills. The judge needs to give reasons or considerations following the values of truth and justice (ratio decidendi). The judge must also use common sense or rational thinking by paying attention to the previous judge's decisions to avoid striking disparity in sentencing. Currently, the judiciary in Indonesia, especially in the Salatiga District Court, still uses the method of imposing sentences based on trial examinations only. This causes court decisions issued by judges to have differences between one decision and another, which is called criminal disparity. The research method used by the researcher was a juridical-normative research method equipped with an in-depth case approach using the ratio decidendi theory. The technique of collecting legal materials used was a literature study. The legal material analysis technique used was deductive data analysis.